After the floods: Differential impacts of rainfall anomalies on child stunting in India. (September 2020) - Dimitrova, Anna; Muttarak, Raya
Highlights: Excessive rainfall increases the risk of child stunting in India. Children from socially disadvantaged households display higher vulnerability to such shocks. Investment in women's education can significantly reduce the risk of child stunting.